Mindfulness and Its Relation to Self Regulated Learning Among University Students - احمد اسماعيل عبود ساندي نصرت فرنسيس (College of Education for Women, 2019)
Mindfulness is considered a process to draw an image of the active event and to creat new social varieties which leaves the individuals open to modernity and to be sensitive towards the context. in contrast, when individuals act with less attention, they need to be more determined concerning the varieties and events of the past . and as a result , they become unaware of the characteristics that creat the individual condition .The problem of the current study is represented in asking about the nature of the possible relationship between mindfulness and self-regulated learning within specific demographic frame of an importantsocial category represented in university students where no previous researches nor theories have agreed on the nature of the relationship between those 2 variables. and no local study-as far as the researcher concerned-has tackled this vital topic within this wide and important class of the society which is the youth . The objectives of the study is as the following: 1- Measuring mindfulness in the study in a sample and to enhance its statistical significance. 2- Measuring mindfulness according to the variables of gender (male-female) and academical disciplines (humanities-sciences) and to enhance their statistical significance. 3 - to identify the nature of the relationship between mindfulness and self-regulated learning in the study sample and to enhance its statistical significance. The study sample is consisted of 400 male and female student selected randomly from 8 colleges in University of Baghdad,4 humanities colleges and 4 sciences colleges.and in order to achieve the objectives of the study,a measurement tool for mindfulness has been prepared in light of the measurements,literary references and previous studies that addressed this variable.and after analyzing the paragraphs using the 2 extreme groups method and the relation of the paragraph degree with the total degree of the measurement tool,all of its 25 paragraphs have been approved which scored stability factor average of (0,71) according to the split-half method and (0,82) according to Cronbach alfa method.and for the second variable,self-regulated learning,the researcher used the self-regulated learning measurement tool which was prepared by Al-Suraifi in 2008.which contains 39 paragraphs in its final form.and its stability was extracted by split-half method with average of (0,85) and Cronbach alfa method (0,93). And heres the summary of the study outcomes : 1-the current study sample have mindfulness 2-there are no differences in mindfulness among university students in terms of the variable of gender (male-female) and academical disciplines (humanities-sciences) and the reaction between them . 3- there is a positive relationship between mindfulness and self-regulated learning in which as self-regulated learning increases,mindfulness increases within university students . And the study concluded with a number of conclusions and recommendations and proposals.